2010
DOI: 10.1103/physrevlett.104.180502
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Gap and a New Principle of Adiabatic Continuity

Abstract: We give a complete definition of the entanglement gap separating low-energy, topological levels, from high-energy, generic ones, in the "entanglement spectrum" of Fractional Quantum Hall (FQH) states. By removing the magnetic length inherent in the FQH problem -a procedure which we call taking the "conformal limit", we find that the entanglement spectrum of an incompressible ground-state of a generic (i.e. Coulomb) lowest Landau Level Hamiltonian re-arranges into a low-(entanglement) energy part separated by a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
207
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(221 citation statements)
references
References 23 publications
12
207
2
Order By: Relevance
“…In contrast, in the orbital cut each entanglement eigenvalue scales as E a − E 0 ∼ L −ζ a , which precludes the possibility of collapsing the spectrum. This is contrary to earlier indications that the orbital spectrum showed the same linear dispersion, 32 though the case studied there was the "conformal limit" of bosonic ν = 1 2 wave function on a finite sphere.…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast, in the orbital cut each entanglement eigenvalue scales as E a − E 0 ∼ L −ζ a , which precludes the possibility of collapsing the spectrum. This is contrary to earlier indications that the orbital spectrum showed the same linear dispersion, 32 though the case studied there was the "conformal limit" of bosonic ν = 1 2 wave function on a finite sphere.…”
Section: Introductioncontrasting
confidence: 55%
“…III, the computational complexity of the MPS representation is on the order O(b L ) for b ∼ O (1). However, to achieve the same type of scaling in the traditional Hilbert space representation (say on a sphere 11,[30][31][32][33][34] would require N ∼ O(L 2 ) particles and a Hilbert space dimension scaling as b L 2 . We note that previously a conceptually distinct approach found an MPS for the Laughlin state in which there is one matrix per particle, rather than per orbital.…”
Section: Introductionmentioning
confidence: 99%
“…[24] (see formula (13) and (14) in that reference where we have defined the boundary perturbation as…”
Section: Discussionmentioning
confidence: 99%
“…[13], and observed that it contains a low-lying part in which the multiplicities are related in a universal way to the ones of the conformal field the-ory (CFT) describing the low-energy edge excitations. This low-lying universal part is usually well-separated from the rest of the ES by an entanglement gap (see also the extended discussion in [14]). LH suggested that this low-lying part could be used as a diagnostic tool when comparing two ground state wavefunctions.…”
Section: A Motivationmentioning
confidence: 99%
“…The single particle entanglement spectrum is closely related to the entanglement entropy 42,[44][45][46] by…”
Section: Single Particle Entanglement Spectrummentioning
confidence: 99%